The Effectiveness of Game-Based Learning using the Duolingo application in enhancing students mastery of passive vocabulary - Siti Indrawati Iin; Farmasari Santi; Junaidi Ahmad; Amin Muhammad (Journal of English Education Forum (JEEF), 2026)
Vocabulary is a crucial aspect in all English language teaching. The greater the vocabulary mastery a person has, the better their language skills and communication abilities. Various strategies, methods, and techniques have been employed by educators to teach vocabulary to students. The use of game-based learning through the Duolingo application offers an alternative for teachers to develop students’ vocabulary, particularly in mastering new words, spelling, pronunciation, and correction. This game is suitable for teachers to incorporate vocabulary teaching into the learning process. This research was conducted to enhance students' mastery of passive vocabulary by implementing game-based learning through the Duolingo application. The study used a quantitative method with a pre-experimental approach, specifically employing a one-group pre-test and post-test design. The population consisted of all tenth-grade students, totaling 287 learners across eight classes. The sample was chosen through a cluster random sampling technique, resulting in 36 students from class E 2. Students completed an initial pre-test, participated in the treatment sessions, and then took a post-test. The results show a significant increase in learners’ passive vocabulary following the use of Duolingo as a game-based learning tool. This improvement is reflected in the rise of the mean score from 39.30 on the pre-test to 80 on the post-test. Additionally, at the 5% significance level, the obtained t-value of 4.43 is higher than the t-table value of 2.030 (4.43 ≥ 2.030) with 35 degrees of freedom. These findings confirm that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. Keywords: Game-Based Learning (GBL), Duolingo Application, Passive Vocabulary.